Rac1 overexpression promotes Treg-derived cytokines to mediate choroidal neovascularization in wet age-related macular degeneration - Juanjuan Li; Yuling Ren; Hua Li; Zhikun Zheng (Brazilian Journal of Medical and Biological Research)
Age-related macular degeneration (AMD), particularly the wet form characterized by choroidal neovascularization, is a leading cause of vision loss. Dysregulation of regulatory T cells (Tregs), key modulators of inflammatory responses, may contribute to wet AMD pathogenesis. This study explored the involvement of Tregs and the Rac1 signaling pathway in modulating Treg-derived cytokine expression and their role in choroidal neovascularization during wet AMD progression. Peripheral blood samples from healthy controls, dry AMD patients, and wet AMD patients were collected. An in vitro transmembrane co-culture system of Tregs and human choroidal endothelial cells (HCECs) was employed to investigate the impact of Tregs (with or without Rac1 silencing) on the angiogenic phenotype of HCECs. A mouse model of AMD was established to evaluate the effects of a Rac1 inhibitor and IL-10/TGF-β neutralization on Tregs and choroidal neovascularization. An increased Treg percentage in the CD4+ T lymphocyte population was found in the peripheral blood samples of wet AMD patients. Tregs from wet AMD patients showed an increased expression of Rac1 and an elevated production of IL-10 and TGF-β1. Rac1 silencing suppressed Treg stability and differentiation, and impaired the pro-angiogenic effect of Tregs on HCECs. In the animal model of AMD, the administration of a Rac1 inhibitor or neutralizing antibodies against IL-10/TGF-β1 reduced Treg abundance and attenuated choroidal neovascularization. Rac1 upregulation in Tregs promoted IL-10 and TGF-β1 production to mediate choroidal neovascularization in wet AMD. Targeting Rac1 and Treg-derived IL-10/TGF-β1 production in Tregs may serve as a strategy to ameliorate AMD progression.